2010
DOI: 10.3146/ps09-016.1
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Economic Returns and Minimizing Stem Rot Incidence with Optimum Plant Stands of Peanut in Nicaragua

Abstract: Peanut growers in Nicaragua use high seeding rates, often greatly in excess of the 19.7 seeds/m recommended for growers in Georgia. Significant yield loss to peanut stem rot (caused by Sclerotium rolfsii) often occurs because of rapid disease spread in high density plant stands. It was hypothesized that lower seeding rates would be beneficial, and field experiments were conducted from 2005 to 2006 in Nicaragua to determine the optimum plant stands for stem rot management, peanut yield, and maximum economic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(19 reference statements)
2
13
0
Order By: Relevance
“…Although stem rot often occurs in rainfed peanut (Watkins, 1961), irrigation can exacerbate the problem (Davis et al, 1996). High soil moisture promotes infection and fungal mycelial spread between and within plants, especially in dense stands resulting from use of high seeding rates (Punja, 1985;Sconyers et al, 2005;Augusto et al, 2010). Infection of S. rolfsii is limited to basal stems, roots, pegs and pods, and colonization of the tissues coincides with beginning peg and beginning pod [R2 and R3 as defined by Boote (1982)] when peanut branches spread rapidly across the soil (Augusto et al, 2010a).…”
mentioning
confidence: 99%
“…Although stem rot often occurs in rainfed peanut (Watkins, 1961), irrigation can exacerbate the problem (Davis et al, 1996). High soil moisture promotes infection and fungal mycelial spread between and within plants, especially in dense stands resulting from use of high seeding rates (Punja, 1985;Sconyers et al, 2005;Augusto et al, 2010). Infection of S. rolfsii is limited to basal stems, roots, pegs and pods, and colonization of the tissues coincides with beginning peg and beginning pod [R2 and R3 as defined by Boote (1982)] when peanut branches spread rapidly across the soil (Augusto et al, 2010a).…”
mentioning
confidence: 99%
“…Similarly, Sconyers et al (2007) reported increased stem rot in plots seeded at 22.6 seeds/m when compared to those seeded at 12.5 and 17.4 seeds/m, respectively. Augusto et al (2010) reported consistent increases in stem rot at increased plant populations in areas with significant levels of the pathogen.…”
mentioning
confidence: 75%
“…In this study, the high-risk model of the Peanut Disease Risk Index (Kemerait et al, 2011) was used at all siteyears resulting in a robust fungicide program for preventative maintenance of incidence and spread of disease, and overall stem rot pressure was low. Augusto et al (2010) reported that a greater number of plants/m of row are allowable without increasing stem rot incidence in areas of low pressure. While they described low incidence as 3% and below, average incidence of 4% in our study was only slightly above that level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern blight often is an issue due to moist conditions brought on by irrigation or rainfall [33,34]. High soil moisture promotes infection and fungal mycelial spread between and within plants, especially in dense stands resulting from the use of high seeding rates such as used in these studies (approximately 16 seed/m) [35][36][37]. Southern blight infection is limited to basal stems, roots, pegs, and pods, and colonization of the tissues coincides with beginning peg and pod formation (R2 and R3) as defined by Boote [38] when peanut branches spread rapidly across the soil [37].…”
Section: Southern Blightmentioning
confidence: 99%